Economic Rationale for Industrial Policy in Developing Countries - Matyáš, David; Klosová, Anna, 1942-; Araujo, Ricardo; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
This thesis goes through basic principles of industrial policy in developing countries and analyses examples of recent industrial policies in BRIC countries (Brazil, Russia, India and China) in the last two decades. The analysis shows the coexistence of unsuccessful and fruitful stories of industrial policy implementation. In the text, I focus especially on the last two decades. I recognize that industrial policy can have a positive impact on economy in some cases, but on the other hand, government failures are frequent and they can result in deep distortions of economic systems and waste of resources. Since 90s', pro-active approach positively contributed to the growth primarily in China and India -- although the progress of these two countries differs substantially. These two countries were (and still are) relatively poorer than Russia and Brazil. Typically, industrial policy in BRIC countries broadly overrides problems of corporate governance, corrupt practices and bureaucratic burdens.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]